2015
DOI: 10.5152/tjg.2015.0150
|View full text |Cite
|
Sign up to set email alerts
|

The last innovation in achalasia treatment; per-oral endoscopic myotomy

Abstract: Background/Aims: Per-oral endoscopic myotomy (POEM) is a minimally invasive endoscopic treatment option for patients with achalasia and has been performed since 2010. It is less invasive than Heller myotomy and its use is spreading rapidly worldwide. We present our results of POEM that, to the best of our knowledge, are the first cases in Turkey. Materials and Methods: We enrolled patients between May 2014 and September 2014; 8 patients with achalasia whose complaints recurred after pneumatic balloon dilatatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…9,12 However, other studies point out that such an application itself immediately before the procedure can lead to aspiration, causing a loss of time and a cost increase. [13][14][15][16] More recent clinical practice guidelines recommend esophageal cleaning before POEM. 17 However, in spite of patients having a 3-day liquid diet and esophageal cleaning 1 day before the procedure in our hospital, 11 of the 220 patients in this study had fluid regurgitation during intubation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,12 However, other studies point out that such an application itself immediately before the procedure can lead to aspiration, causing a loss of time and a cost increase. [13][14][15][16] More recent clinical practice guidelines recommend esophageal cleaning before POEM. 17 However, in spite of patients having a 3-day liquid diet and esophageal cleaning 1 day before the procedure in our hospital, 11 of the 220 patients in this study had fluid regurgitation during intubation.…”
Section: Discussionmentioning
confidence: 99%
“…During submucosal tunneling and myotomy in the esophagus, rapid mediastinal and peritoneal absorption of carbon dioxide may cause pneumomediastinum, cervical/thoracic subcutaneous emphysema, and pneumoperitoneum. 9,15,16 Lack of sufficient barrier formation in the esophagus muscle fibers and adventitia contributes to rapid absorption of CO 2 . In fact, Yang and colleagues identified high rates of pneumomediastinum (37.0%), pneumoperitoneum (43.5%), and subcutaneous emphysema (29.6%) on postoperative computed tomography scans of 108 POEM patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These treatments aim to ease the passage of food from the esophagus to the stomach and to relieve any symptoms by reducing the lower esophageal sphincter pressure (LESP). 2 - 4 People are more likely to have multiple comorbidities together with increased average life expectancy. It has been reported that approximately 65% of patients in the geriatric age group have 3 or more comorbid diseases.…”
Section: Introductionmentioning
confidence: 99%